AN ANALYSIS AND DESIGN OF DECISION SUPPORT SYSTEMS FOR SUGAR CANE HARVESTING (CASE STUDY IN PT. RAJAWALI II UNIT PG. JATITUJUH, MAJALENGKA) - Aldian Farabi dan Machfud (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT PT. Rajawali II Unit PG. Jatitujuh is the company which process sugar canes become first quality Super High Sugar (SHS I). The harvesting of sugar cane has been done on summer in order to gain optimum yield. Daily scheduling of sugarcane has been done in order to fulfill the raw material of factory continously. This scheduling has been done toward the sugarcane field with area of 11.921,56 ha and spread on the 2.418 of swath. Nowadays, the scheduling of daily harvesting has been decided through Harvesting Forum Meeting(Rapat Forum Tebang) based on age of sugar canes, the highest yield, and subjectively actual condition of sugar canes field. This method is still done manually with separated database system. Axe DSS 1.0 is a support system to make decision in harvesting of sugar canes with real-time refers to modificated T-Score method. The decision support system (DSS) is developed based on Unified Modelling Language (UML) which consists of case diagram, activity diagram, class diagram, and statechart diagram. Axe DSS uses java programing language which consists of 3 sub-system, which are harvesting sample, analysis result, and daily harvesting. Input of this system are data cane planted last year, preface analysis, actual condition of sugar canes fields and factory. Then the data is managed with cane sugar analysis calculation and modify T-Score calculation. While ,the output of this system are sample field, analysis result, and next day harvesting cane schedule. This prototype has several advantages which are faster decision-making, flexible, automatic report printing, and faster data storing and searching compare with manual decision-making. Keywords: DSS, realtime, scheduling, sugarcane, T-Score, UML